(untitled) (Patan Pragya, 2025)
Traditional rhetoric is largely concentrated on the soundness of logical arguments with the goal of persuading the audience. Silence is often rendered as absence of meaning, thus regarded as a lack in the communication process. However, the purpose of this research is to analyze silence in Damon Galgut’s The Promise as a rhetorical art with the goal of establishing understanding between the communication parties. Furthermore, it analyzes how the writer has established silence as a means to negotiate with the racial disharmony in South African post-apartheid society. To do this, the article builds upon the theoretical frameworks developed by Cheryl Glenn and Kennan Ferguson which foreground silence as a rhetorical art. The study finds that the novel presents silence as an alternative rhetoric through the silences of two major characters Salome and Amor. Salome’s silence coalesces with her lack of agency whereas Amor deploys silence to constitute her individual space, disavow and resist the injustice of her family and come to terms with Salome’s unprivileged condition. The research helps to understand how rhetorical silence can be useful in bridging the rift caused by racial discordance in particular and to initiate proper communication in situation of complex cultural antagonisms.